Financial Performance Segmentation Changes on Regional Development Banks - Isfan Ferli; Jerry Heikal (Universitas KH. Abdul Chalim Mojokerto, 2024)
Merger and acquisition of a banking company are generally understood as efforts to enhance the company by combining strengths or compensating for the weaknesses of one company with the strengths of another. To face the dynamics of the domestic and global economy and information technology, it is necessary to strengthen the structure, resilience, and competitiveness of the national banking industry, which can be achieved by strengthening bank capital and banking consolidation in Indonesia, especially Regional Development Banks. To promote the stability of the banking industry, particularly the strengthening of individual banks, merger and acquisition strategies in the form of banking consolidation need to be considered. Banking consolidation policies are one of the policy options regulators take to strengthen financial system stability. One of the processes that must be carried out is analyzing the performance to find companies that are suitable for acquisition, in accordance with the problem statement: How is the performance of the Regional Development Banks that become acquiring banks, and how is the performance of Regional Development Banks whose core capital does not yet meet regulatory requirements, making them suitable for acquisition. Data from 27 Regional Development Banks were analyzed based on several financial ratios, namely ROA, ROE, NIM, LDR, CAR, and NPL, and the changes in economic performance into five clusters using IBM SPSS version 27 with K-Mean Cluster Classification. The analysis showed that out of the 27 Regional Development Banks, 11 banks experienced a status increase, 10 companies experienced a decrease, and 6 did not change. It was found that the performance of 4 Regional Development Banks that would become acquiring banks is